2010
DOI: 10.1016/j.marpolbul.2010.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of benthic foraminifera and macrofaunal indicators of the impact of oil-based drill mud disposal

Abstract: We compare foraminifera and macrofauna as bio-indicators of oil-based drill mud disposal site off Congo. The most polluted sites are characterized by poor faunas, dominated by some very tolerant taxa. Slightly further from the disposal site, there is an area with strongly increased densities, heavily dominated by opportunistic taxa. Still further, macrofauna appears to be similar to that at the reference area, but the foraminiferal meiofauna still suggests a slight environmental perturbation. The foraminiferal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 68 publications
2
35
1
3
Order By: Relevance
“…The environmental impact of weathered crude oil on benthic foraminifera in an Atlantic coastal salt marsh was evaluated by Sabean et al (2009), who demonstrated the negative impact of oil on foraminiferal assemblages, as testified by a dramatic increase in abnormalities in Miliammina fusca when compared with the non-oiled control. Meanwhile, benthic foraminifera and macrofauna were evaluated as bio-indicators of an oil-based drill mud disposal site off Congo (Denoyelle et al, 2010). Poor faunas, dominated by some very tolerant taxa at the most polluted sites, were found, whereas greatly increased densities thereof, dominated by opportunistic taxa, were identified slightly further away from the disposal site.…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…The environmental impact of weathered crude oil on benthic foraminifera in an Atlantic coastal salt marsh was evaluated by Sabean et al (2009), who demonstrated the negative impact of oil on foraminiferal assemblages, as testified by a dramatic increase in abnormalities in Miliammina fusca when compared with the non-oiled control. Meanwhile, benthic foraminifera and macrofauna were evaluated as bio-indicators of an oil-based drill mud disposal site off Congo (Denoyelle et al, 2010). Poor faunas, dominated by some very tolerant taxa at the most polluted sites, were found, whereas greatly increased densities thereof, dominated by opportunistic taxa, were identified slightly further away from the disposal site.…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…Previous studies showed that foraminiferal communities rapidly change under organic pollution exposures associated with fish farming (Scott et al 1995, Angel et al 2000, Vidovi et al 2009. Foraminifera are also good indicators of the impact of offshore drilling activities (Mojtahid et al 2008, Jorissen et al 2009, Denoyelle et al 2010, Schwing et al 2015 and heavy metal pollution (Bergin et al 2006, Frontalini et al 2009). However, all of these studies were restricted to the hard-shelled species microscopically identified in dried sediment samples (Schön -feld et al 2012, Alve et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Foraminiferal studies have been very useful in the field of coastal sciences (Scott et al, 2014) and have contributed to a better understanding of the phenomena that shaped the ocean in the past (Hayward et al, 2001) and in the present (Havach and Collins, 1991;Denoyelle et al, 2010;Youssef, 2015). Foraminifera are commonly small in size and extremely abundant in almost all marine environments, even when a small amount of sample is available (Ratcliffe and Zaitlin, 2010).…”
Section: Introductionmentioning
confidence: 99%